2017
DOI: 10.17085/apm.2017.12.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of the addition of intrathecal fentanyl to bupivacaine for spinal anesthesia in cesarean section

Abstract: Background: The addition of fentanyl or epinephrine to bupivacaine enhances the quality of intraoperative spinal anesthesia during cesarean section. This study aimed to evaluate the beneficial effects of adding fentanyl or epinephrine to bupivacaine in spinal anesthesia solutions used for patients undergoing cesarean section. Methods: This retrospective study included 391 patients who underwent cesarean section under spinal anesthesia between March 2009 and February 2014. Parturients were categorized into grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Although there have been skeptical opinions about spinal anesthesia in the past, including reports of low cord pH in fetuses born from spinal anesthesia [ 6 8 ], several studies have been conducted on the treatment of post-spinal anesthesia hypotension ever since, and the complications of spinal anesthesia have gradually decreased [ 9 ]. Additionally, a previous study has identified the positive effect of administering intrathecal opioids for postoperative pain [ 10 , 11 ], with high satisfaction as parturients were able to ambulate faster after the operation when spinal anesthesia, rather than general anesthesia, was administered [ 12 ]. Spinal anesthesia is also more economically beneficial compared to epidural anesthesia [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been skeptical opinions about spinal anesthesia in the past, including reports of low cord pH in fetuses born from spinal anesthesia [ 6 8 ], several studies have been conducted on the treatment of post-spinal anesthesia hypotension ever since, and the complications of spinal anesthesia have gradually decreased [ 9 ]. Additionally, a previous study has identified the positive effect of administering intrathecal opioids for postoperative pain [ 10 , 11 ], with high satisfaction as parturients were able to ambulate faster after the operation when spinal anesthesia, rather than general anesthesia, was administered [ 12 ]. Spinal anesthesia is also more economically beneficial compared to epidural anesthesia [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…29 Whereas in another study incidence of pruritus was nil. 30 In another study by kuusniemi et al 31 , they observed that pruritus was the most common adverse effect, occurring in 22.5% of all patients after intrathecal fentanyl.…”
Section: Group a Group Bmentioning
confidence: 95%